MEKANISME PEMUNGUTAN DAN PENAGIHAN PAJAK RESTORAN STUDI KASUS KANTOR BADAN KEUANGAN DAERAH KOTA BANJARMASIN - arfianti; Muhammad Riza Firdaus (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
This final report aims to explain how the mechanism of the restaurant tax collection and collection system at the Banjarmasin City Regional Finance Office. The conclusions of this study are: Restaurant tax collection is carried out every month after payment to restaurants. While the system used in collecting restaurant taxes is a Self Assessment system where the collection system is determined by the taxpayer himself by paying directly to the Banjarmasin City Regional Finance Office or depositing directly to the regional treasury through a bank.